1971
DOI: 10.1177/001316447103100429
|View full text |Cite
|
Sign up to set email alerts
|

A Multitrait-Multimethod Validation of Measures of Student Attitudes Toward School, Toward Learning, and Toward Technology in Sixth Grade Children

Abstract: EDUCATORS and parents are becoming increasingly aware of the importance of student attitudes. The child is often expected not only to learn the required subject matter, but also to enjoy school and to look forward to learning new things. Also, there is concern among industrial leaders as well as educators that children appreciate the benefits of technology and that they not be afraid of the many machines in their environments. Previous studies (Coleman, Campbell, Hobson, McPartland, Mood, Weinfeld, and York, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
2

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…Correlational studies in several areas have demonstrated a significant positive relationship between how interesting children say they find particular educational materials and how much they learn and recall from those materials (e.g., Ascher, 1979;Anderson, Shirey, Wilson, & Fielding, 1987). A favorable attitude towards the various subject matters taught in school also appears to be positively correlated to academic success (Brodie, 1964;Roshal, Frieze, & Wood, 1971;Haladyna & Thomas, 1979). Nevertheless, these studies contain no evidence indicating that the degree of interest students show in the material is a determinant, and not a consequence, of its learning.…”
Section: Introductionmentioning
confidence: 94%
“…Correlational studies in several areas have demonstrated a significant positive relationship between how interesting children say they find particular educational materials and how much they learn and recall from those materials (e.g., Ascher, 1979;Anderson, Shirey, Wilson, & Fielding, 1987). A favorable attitude towards the various subject matters taught in school also appears to be positively correlated to academic success (Brodie, 1964;Roshal, Frieze, & Wood, 1971;Haladyna & Thomas, 1979). Nevertheless, these studies contain no evidence indicating that the degree of interest students show in the material is a determinant, and not a consequence, of its learning.…”
Section: Introductionmentioning
confidence: 94%
“…Negligee en effet parce que, comme le soulignent Haladyna et Thomas (1979), «Ia mesure systematique de l'attitude des eleves face iJl'ecole et aux differentes matieres constituant son programme s'est rivelee manifestement tres rare». 'Ires importante en revanche puisque, lorsque cette mesure a ete effectuee, on a toujours releve un lien positif entre une attitude favorable al'ecole comme ases differentes matieres et la reussite scolaire (e. g. Brodie, 1964;Roshal et al, 1971;Haladyna & Thomas, 1979).…”
Section: Michel Chambonunclassified
“…Negligee en effet parce que, comme le soulignent Haladyna et Thomas (1979), «Ia mesure systematique de l'attitude des eleves face iJl'ecole et aux differentes matieres constituant son programme s'est rivelee manifestement tres rare». 'Ires importante en revanche puisque, lorsque cette mesure a ete effectuee, on a toujours releve un lien positif entre une attitude favorable al'ecole comme ases differentes matieres et la reussite scolaire (e. g. Brodie, 1964;Roshal et al, 1971;Haladyna & Thomas, 1979).Toutefois, ainsi posee en terme d'attitude, l'approche de la perception des contenus scolaires se trouve de la sorte circonscrite au recueil de l'expression evaluative d'un etat affectif interne aI'Individu-eleve: «J'aime/je n'aime pas l'ecole» -«J'aime/je n'aime pas I'Histoire--Geographie, les Mathematiques ou le Dessin». Par ailleurs et d'une maniere assez proche, le meme probleme est egalernent evoque et traite dans le domaine pedagogique en termes d'interets ou de motivation, Iaquelle est elle aussi definie comme un etat interne, resultat d'une tension psychologique suscite par l'objet de reference (Leif & Delay, 1965, p. 376).…”
unclassified
“…CT-CM Figure 1 Table 3 CT-C(M 1) 2 MTMM 12 Biesanz & West 2004, Carroll 1952, Coenders & Saris 2000, Kelly & Fiske 1951, Kothandapani 1971, Levin 1973, Maas, Lensvelt-Mulders, & Hox 2009, Manson, Levine, & Brannick 2000, Muis, Winne, & Jamieson-Noel 2007, Ostrom 1969, Roshal, Frieze, & Wood 1971, Steger, Frazier, Oishi, & Kaler 2006 Table 4 Table 7 4 Table CT T1 T2 T3 T4 T5 M1 1 M2 2 M3 3 T1, ,T5 M1, ,M3 MTMM …”
mentioning
confidence: 99%